Is the POLST Model Desirable for Florida? - Sarah Catherine Spillers; Brittany Lamb (University of North Florida, 2011)
Florida has one ofthe largest and most rapidly growing elderly populations in the nation. Although advances in medicine are allowing physicians to extend the lives of elderly patients, advances must simultaneously be made in the end-of-life care arena to ensure that the comfort and quality of life of elderly patients is maintained. This paper argues that use of a Physician Orders for Life Sustaining Treatment (POLST) form in Florida would be effective in increasing the accuracy oftranslating patients' end-of-life wishes into treatment orders, in ensuring the consistency of treatment across settings, and in improving health care provider compliance with patient preferences. It will be demonstrated that present concerns in Florida are essentially the same as those which previously existed in other states that have successfully implemented POLST programs.